Analisis Penggunaan Konjungsi Koordinatif Pada Rubrik Politik Dalam Surat Kabar Kompas Edisi Januari 2016 Sebagai Materi Pembelajaran Bahasa Indonesia Di SMP - Novita, Reni; , Prof. Dr. Abdul Ngalim, M.M.,M.Hum (2016)
This research there are three objectives to be achieved. (1) Describes the kind of coordinating conjunctions in the political section in the newspaper Kompas January 2016. (2) Describe the use of conjunctions coordinated at the political section in the newspaper Kompas January 2016. (3) Describe conjunctions at the level of word, phrases, clauses, and sentences. This study uses descriptive method qualitative research in the form of qualitative the data collected and analysis is qualitative. The methods and techniques used in this research is data collection methods and techniques refer to the note. Data analysis methods used in the form agih method. Agih method is a tool that determining precisely the relevant part of the language itself. Advanced technique used method is a technique agih read many. Read many techniques used in this study serves basic viewing pemarkahan associated with lingual information. The results of this study show that the political section in the newspaper Kompas there are 5 types of coordinative conjunctions and use. 1) The sum coordinative conjunctions such as and, with as well. 2) Type the election form or coordinative conjunctions. 3) Type a coordinating conjunction, opposition in the form of yet, but, meanwhile. 4) Type coordinating conjunctions be even, moreover, do not. 5) Type coordinating conjunctions such sorting later, then. The use of coordinative conjunctions in the political section in the newspaper Kompas can be used as materials and examples of Indonesian language learning in junior high. This proves that the newspaper had not only serve as entertainment only, but can be used as learning materials Indonesian.